Investigating Fintech Service Adoption using Extended-ECM - Bernardinus Harnadi; Albertus Dwiyoga Widiantoro; FX Hendra Prasetya (Soegijapranata Catholic University, 2022)
This paper aims to investigate the Fintech Service Acceptance on Student in Indonesia. The investigating of the acceptance employs extended-ECM to reveal the student’s perception of usefulness, confirmation, and satisfaction in using fintech service. The extend of Expectation–confirmation model (ECM) using technological self-efficacy (TSE) and perceived ease of use is used in this research to investigate the adoption study in fintech area. This research also adds trust factor to fit up the investigation in the area. The 302 questionnaires from respondents are tested using SmartPLS to point significantly factors in the proposed model. The results reveal that the factors in ECM and trust are most powerful in fintech service acceptance study. The interesting result came from TSE as a predicted factor for confirmation and perceived ease of use and not for perceived usefulness. The results have recommendation to developer of fintech application. They must aware to technological self-efficacy of users.